Trousseau syndrome and ovarian cancer - E.F. Kalinkina; N.P. Sluvko; O.V. Kondrat'eva; D.G. Tarasov (LCC «Medicine-Inform», 2020)
E.F. Kalinkina1, N.P. Sluvko2, O.V. Kondrat'eva1, D.G. Tarasov1,3 1Federal Center for Cardiovascular Surgery (Astrakhan), Astrakhan, Russian Federation 2Regional Oncological Dispensary, Astrakhan, Russian Federation 3Astrakhan State Medical University, Astrakhan, Russian Federation Migratory thrombophlebitis is a rare paraneoplastic syndrome occurred in malignancies. The association between migratory thrombophlebitis and malignancy is known as Trousseau syndrome. Thrombotic complications preceding malignancy manifestation are referred to as thrombotic mask. This paper describes successful surgical outcome of ovarian cancer associated with Trousseau syndrome. The first manifestations of this syndrome were acute proximal thrombosis in the left popliteal and left femoral vein, spontaneous arterial thrombosis, and numerous intracranial thromboses that have resulted in myocardial infarction and ischemic stroke. Later, the woman was diagnosed with ovarian cancer (T1aN0M0). All paraneoplastic signs have disappeared after a surgery for ovarian cancer. Congenital thrombophilia was an additional risk factor for thrombosis. The woman was provided with surgical, anesthetic, and intensive medical care which have improved the quality of life, increased life expectancy , and returned workability. Keywords: ovarian cancer, paraneoplastic syndrome, Trousseau syndrome, thrombotic complications, hemostasis disorders. For citation: Kalinkina E.F., Sluvko N.P., Kondrat'eva O.V., Tarasov D.G. Trousseau syndrome and ovarian cancer. Russian Journal of Woman and Child Health. 2020;3(2):95-99. DOI: 10.32364/2618-8430-2020-3-2-95-99.